A methodology to predict shock overpressure decay in a tunnel produced by a premixed methane/air explosion. (November 2016) - Zhang, Qi; Qin, Bin; Yan, Hua; Lin, Da-Chao
Abstract: A methodology for estimating the blast wave overpressure decay in air produced by a gas explosion in a closed-ended tunnel is proposed based on numerical simulations. The influence of the tunnel wall roughness is taken into account in studying a methane/air mixture explosion and the subsequent propagation of the resulting shock wave in air. The pressure time-history is obtained at different axial locations in the tunnel outside the methane/air mixture. If the shock overpressure at two, or more locations, is known, the value at other locations can be determined according to a simple power law. The study demonstrates the accuracy of the proposed methodology to estimate the overpressure change with distance for shock waves in air produced by methane/air mixture explosions. The methodology is applied to experimental data in order to validate the approach. Highlights: A methodology for estimating blast wave of a gas explosion in a closed-ended tunnel is proposed. A practical approach for analyzing the accident induced by a methane/air mixture explosion in a tunnel is provided. Overpressure attenuation of a gas explosion in a closed-ended tunnel with distance obeys the exponent law.